The impact of COVID-19 pandemic on AIDS-related mycoses and fungal neglected tropical diseases: Why should we worry? - Sanaz Nargesi; Felix Bongomin; Mohammad T Hedayati (Public Library of Science (PLoS), 2021)
The World Health Organization (WHO) considers mycetoma, chromoblastomycosis, and paracoccidioidomycosis to be fungal neglected tropical diseases (FNTDs). Depending on climatic, cultural, and economic contexts, these diseases have a similar geographical distribution as many other diseases, particularly tuberculosis (TB) and malaria, but are often less targeted by the national and many international healthcare systems. Another subgroup of fungal infections, such as candidiasis, cryptococcosis, pneumocystosis, histoplasmosis, and to a lesser extent, aspergillosis, are known as AIDS-related mycoses. Although antiretroviral therapy (ART) has been able to decrease the mortality rate of these diseases, particularly cryptococcosis, the disproportionately low distribution of funds to their diagnosis and treatment remains an obstacle in saving and improving the lives of patients affected. A new wave of viral diseases dubbed the Coronavirus Disease 2019 (COVID-19) hit the world at the end of 2019. Due to progressive symptoms and high mortality rates of COVID-19 compared to fungal infections, particularly the FNTDs, funding is currently allocated predominantly for diagnostic and therapeutic research on COVID-19. As a result, advances in FNTDs and AIDS-related mycosis care are considerably reduced. This paper explores the association between COVID-19, FNTDs, and AIDS-related mycoses with a predictive perspective.